Warfare in independent Africa - Reno, William, 1962- (Cambridge ; New York : Cambridge University Press, 2011)
"This book surveys the history of armed conflict in Africa in the pe riod since decolonization and independence"--
"This book surveys the history of armed conflict in Africa in the pe riod since decolonization and independence. The number of post-independ ence conflicts in Africa has been considerable, and this book introduce s to readers a comprehensive analysis of their causes and character. Tr acing the evolution of warfare from anti-colonial and anti-apartheid ca mpaigns to complex conflicts in which factionalized armies, militias, a nd rebel groups fight with each other and prey upon non-combatants, it allows the readers a new perspective to understand violence on the cont inent. The book is written to appeal not only to students of history an d African politics, but also to experts in the policy community, the mi litary, and humanitarian agencies"--
Machine generated contents note: 1. The evolution of warfare; 2. Ant i-colonial rebels; 3. Majority rule rebels; 4 Reform rebels; 5. Warlord rebels; 6. Parochial rebels; Conclusion: the past and future of warfar e in Africa.
Includes bibliographical references (p. 257-262) and index.
Keywords: Violence -- Africa -- History -- 20th century; Africa -- History, Military -- 20th century; Africa -- History -- 1960-